The Distribution of Dissolved Methane and Its Air-Sea Flux in the Plume of a Seep Field, Lingtou Promontory, South China Sea. (14th July 2019) - Di, Pengfei; Feng, Dong; Chen, Duofu
Abstract : Methane (CH4 ), the most abundant hydrocarbon gas in the atmosphere, plays an important role in global climate change. Quantifying the dissolved methane and its air-sea flux from hydrocarbon seeps is therefore of great importance. Large quantities of natural gas are emitted from the seafloor to the coastal ocean near the Lingtou Promontory, South China Sea. We quantified concentrations of methane in surface and bottom waters at 48 stations in a 56 km 2 study area. High spatial variability in dissolved methane concentrations was observed in the surface mixed layer (0.5 m water depth) and bottom water (water-sediment interface), with values ranging from 2.90 nmol L −1 to 13570.02 nmol L −1 and from 4.98 nmol L −1 to 31740.02 nmol L −1, respectively. The significant difference between concentrations of dissolved methane in surface and bottom waters suggests that most of the methane emitted from the seafloor is dissolved in the water column. The dissolution of methane in seawater may result in local oxygen depletion that may lead to ecological effects. The δ 13 C values of dissolved methane ranging from −59.76‰ to −48.59‰ indicate a mixture of biogenic and thermogenic gas sources. The average air-sea methane flux of Yinggehai Basin was 672.57 μ mol m −2 d −1, which cannot be ignored in environment assessment. Coastal regions, especially with hydrocarbon seeps in shallow waters of the continental margin, may therefore be an important source of methane to the atmosphere.